The invisible, the alien and the marginal: Social and cultural constructions of male rape in voluntary agencies - Javaid, Aliraza (International review of victimology, 2019)
Drawing on a Foucauldian approach and on interview data including male rape counsellors, therapists and voluntary agency caseworkers (N=70), the author attempts to make sense of the different ways in which male rape is constructed in order to better understand how it is considered and responded to in current English society. The qualitative data herein, which were collected through semi-structured interviews and qualitative questionnaires, are theoretically and conceptually informed. The author argues that male rape is socially and culturally constructed in voluntary agencies in England and shaped by discourse, power and knowledge. For example, discourse on male rape is constructed and reconstructed through social and power relations, and through social interactions between voluntary agency practitioners and male rape victims, accompanied by the attendant social structures and social practices. The implication of these arguments is that the voluntary agency practitioners think about and respond to male rape victims in an inconsistent, unpredictable and variable way, meaning that the practitioners are reliant on different discourses and cultural myths about male rape when providing support and services for male rape victims.